Germination response of local Southern European populations of Datura stramonium at a range of constant temperatures. (26th March 2014) - Loddo, D; Sousa, E; Masin, R; Calha, I M; Zanin, G; Fernández‐Quintanilla, C; Dorado, J; Davis, Adam
Summary Studies on weed germination are required to develop efficient integrated weed management strategies that should be transferable at wide scale and accurate at local level. To study interpopulation variability, which may hamper this process, three local populations of Datura stramonium were collected in Italy, Portugal and Spain and then cultivated simultaneously in three common gardens under different environmental conditions. Hence, nine seed lots were included in the germination tests performed at a range of constant incubating temperatures. Significant effects of population of origin, cultivation site, incubating temperature and their interaction were detected on mean germination percentage and germination t50. Mean germination percentage varied from 0.0 to 89.7% ± 2.10 SE at 8 and 20°C respectively. Mean germination t50 ranged from 636.1 ± 24.86 SE to 267.0 ± 16.06 SE hours at 12 and 20°C respectively. Seed lots deriving from the Portuguese population presented the lowest germination percentages and highest germination t50 at low incubating temperatures, regardless of the cultivation site. This behaviour could be related to an adaptive process of the Portuguese population to the local environmental conditions, produced by the combination of climate and agronomic management. The presence of high interpopulation variability for D. stramonium could hinder the development of transferable IWM strategies. However, management plans could be proposed at regional scale according to the approach of modifying the patterns of agronomic disturbances to which the local populations have adapted.